Comparative Study of Neck Swelling by Clinical, Cytological and Histopathological Examination (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: In this study 50 patients of neck swelling were studied to compare the findings with clinical diagnosis and histopathological report for its diagnostic compatibility.Methods: This cross sectional study was done in Department of Otolaryngology –Head & Neck Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka from July 2015 to June 2017. Fine needle aspiration cytology, MRI, CT scan, and histopathological examination of postoperative specimen of neck swelling, analyzed data presented by various tables, graphs and figures.Results:In the present series 50 cases of neck swelling were studied. Out of these 50 cases 19 were male and 31 were female. The male, female ratio was 1:1.63. Age range was 4 – 60 years with maximum frequency in the 4th decade with the 3rd and 2nd in the following suit. Most of the patient were poor. Clinical, cytological and histopathological diagnosis were available in all the cases. The three sorts of diagnoses were compared with each other. Histopathologically 12 cases were tubercular lymphadenopathy. Metastatic carcinoma and lymphoma 5 cases for each. Twelve were nodular goiter, 5 were thyroid carcinoma. Rest were benign, congenital and nonspecific inflammatory conditions. Correct diagnosis were made by FNAC in 45 cases. In the rest 5 cases smear were unsatisfactory in 2 cases and gives inconclusive result, remaining 3 were follicular neoplasm and no definitive result were made which were subsequently diagnosed by histopathological examination as a follicular adenoma in 1 and follicular carcinoma in 2. Sensitivity of FNAC in the diagnosis of neck masses were found 91% for tuberculosis, 100% for metastatic carcinoma also for salivary gland tumour. In case of nodular goiter sensitivity was 92%. But it is only 60% sensitive in case of thyroid malignancy, as FNAC can not demarcate clearly between follicular adenoma and follicular cell carcinoma. But its accuracy in diagnosing papillary cell carcinoma of thyroid was 100%.Conclusion: Keeping the limitations in mind, FNAC can reduce substantially the need of open biopsy for histopathological examination. Last of all I wish to conclude the study with the popular saying of Stewart “Diagnosis by aspiration is as reliable as the combined intelligence of the clinician and pathologist makes it”.Bangladesh J Otorhinolaryngol; April 2020; 26(1): 24-30